Recovery Rates From Distressed Debt : Empirical Evidence From Chapter 11 Filings, International Litigation, and Recent Sovereign Debt Restructurings - Singh, Manmohan (IMF Working Papers; Working Paper ;, 2003)
On a credit rating-adjusted basis, spreads on U.S. high-yield debt have typically been regarded as a lower bound for emerging market debt. However in the C-rated and defaulted segment, emerging market debt has traded at lower spreads than similarly rated U.S. high yield debt. We show that the lower spreads reflect the fact that the total returns from defaulted debt in the emerging markets have been significantly higher than returns from similarly rated high yield defaulted debt under Chapter 11.